Analysis of Vocational Education Policy in the Context of Artificial Intelligence Disruption and Its Implications for the Merdeka Curriculum - Muis, Rizal Rahmawan; Nadhiroh, Nadhiroh; Yasin, Roby Lafadza; Duryat, Masduki; Suherman, Aris (CV. Strata Persada Academia, 2025)
This study aims to analyze vocational education policy in Indonesia in the context of Artificial Intelligence (AI) disruption and to examine its implications for the implementation of the Merdeka Curriculum. Employing a descriptive qualitative approach and content analysis of policy documents, scholarly publications, and research reports, this study explores the dynamics of vocational education policy in response to the digital transformation driven by AI. The findings reveal that Indonesia's vocational education policy is still in its early stages of integrating AI technologies into curricula and instructional practices. Although the Merdeka Curriculum offers flexibility, it has not yet systematically incorporated AI-related competencies, leaving graduates inadequately prepared for the increasingly digitized labor market. Compared to countries such as Germany and South Korea, Indonesia lags behind in establishing AI-based vocational training through strong industry-education collaboration. To address these challenges, three strategic actions are recommended: revising the curriculum to include AI literacy, strengthening industry partnerships through dual training programs and teacher certification, and investing in equitable digital infrastructure. This study offers both conceptual and practical contributions to the development of adaptive, responsive, and future-oriented vocational education policies in the era of technological disruption.